Rapid and Controllable Synthesis of Nanocrystallized Nickel‐Cobalt Boride Electrode Materials via a Mircoimpinging Stream Reaction for High Performance Supercapacitors. Issue 39 (28th August 2020) - Zhang, Qingcheng; Zhao, Junping; Wu, Yechao; Li, Jun; Jin, Huile; Zhao, Shiqiang; Chai, Lulu; Wang, Yahui; Lei, Yong; Wang, Shun
Abstract: Nickel‐cobalt borides (denoted as NCBs) have been considered as a promising candidate for aqueous supercapacitors due to their high capacitive performances. However, most reported NCBs are amorphous that results in slow electron transfer and even structure collapse during cycling. In this work, a nanocrystallized NCBs‐based supercapacitor is successfully designed via a facile and practical microimpinging stream reactor (MISR) technique, composed of a nanocrystallized NCB core to facilitate the charge transfer, and a tightly contacted Ni‐Co borates/metaborates (NCBi ) shell which is helpful for OH − adsorption. These merits endow NCB@NCBi a large specific capacity of 966 C g −1 (capacitance of 2415 F g −1 ) at 1 A g −1 and good rate capability (633.2 C g −1 at 30 A g −1 ), as well as a very high energy density of 74.3 Wh kg −1 in an asymmetric supercapacitor device. More interestingly, it is found that a gradual in situ conversion of core NCBs to nanocrystallized Ni‐Co (oxy)‐hydroxides inwardly takes place during the cycles, which continuously offers large specific capacity due to more electron transfer in the redox reaction processes. Meanwhile, the electron deficient state of boron in metal‐borates shells can make it easier to accept electrons and thus promote ionic conduction. Abstract : A promising core–shell nanostructure with a nanocrystallized Ni‐Co boride core and a tightly encapsulated Ni‐Co metaborate/borate shell (NCB@NCBi ) is synthesized in a microimpinging stream reactor, which exhibits a large specific capacity (966 C g −1 at 1 A g −1 ), good rate capability (633.2 C g −1 at 30 A g −1 ), and a high energy density of 74.3 Wh kg −1 in an asymmetric supercapacitor device.